DESIGN AND DEVELOPMENT OF COMPANY PERFORMANCE ASSESSMENT APPLICATION BASED ON WEBSITE USING THE BALANCE SCORECARD METHOD ON CV MARVELL SEKURINDO - Alvin Mahendra perkasa; Dewiyani Sunarto; I Gusti Ngurah Alit Widana Putra (Jurnal Sistem Informasi Universitas Dinamika, 2021)
Abstract: CV Marvell Sekurindo is a private company engaged in the sale of security systems. In the performance appraisal process so far it has been carried out with manual assessments and the absence of a system to integrate all branches in the absence of a performance appraisal method, in the absence of an appraisal method at the current company the owner will find it difficult to make a comparative assessment of all branches in terms of development, so that resulting in the absence of calculations from the perspective of 4 assessable perspectives, namely financial, customer, internal business, and growth perspectives. The proposed solution given by the author is a web application with the Balance Scorecard method that can simplify the assessment process with nominal results or numbers for comparison in the assessment of each branch in terms of performance appraisal. The Scrocecard Balance method can help admins get data information for each branch faster or more effectively. This application will provide an easy-to-use display for the admin to carry out the calculation process and a comparison system for the various branches of the company because this application can be integrated or connected between branches and other branches. Each branch of the company has 5 employees, namely 1 admin, 1 supervisor and 3 sales service employees at the branch who will be given 1 admin to input the assessment and 1 supervisor to input the master data at the branch. Based on the results of trials conducted with the owner or company owner, this application can make it easier for owners to see the results of developments or performance assessment reports at each branch that have been carried out by their employees.Keywords: Sistem, Informasi, Balance Scorecard, Penilaian Kinerja, Aplikasi